In vitro analysis of anti-HPA-1a dependent platelet phagocytosis and its inhibition using a new whole blood phagocytosis assay (WHOPPA) - Ames, Paula; Baal, Nelli; Speckmann, Martin; Michel, Gabriela; Ratke, Judith; Klesser, Christina; Cooper, Nina; Takahashi, Daisuke; Bayat, Behnaz; Bein, Gregor; Santoso, Sentot (Frontiers in Immunology, 2023)
Fetal and neonatal alloimmune thrombocytopenia (FNAIT) is a serious bleeding condition mostly caused by the reaction between maternal anti-HPA-1a antibodies and fetal platelets. This reaction leads to Fc-dependent platelet phagocytosis. Although several serological methods have been developed to identify maternal antibodies, a reliable laboratory parameter as a prognostic tool for FNAIT severity is still lacking.In this study, we developed whole blood platelet phagocytosis assay (WHOPPA), a flow cytometry-based phagocytosis assay that uses a pH-sensitive fluorescent dye (pHrodo-SE) to analyze anti-HPA-1a-dependent platelet phagocytosis in whole blood.WHOPPA revealed a high phagocytosis rate for the anti-HPA-1a opsonized platelets by monocytes but not by neutrophils. Analysis of different monocyte populations showed that all monocyte subsets, including classical (CD14 ++ CD16 − ), intermediate (CD14 ++ CD16 + ), and nonclassical (CD14 + CD16 ++ ) monocytes, were able to engulf opsonized platelets. A unique monocyte subset, termed shifted monocytes (CD14 + CD16 − ), showed the highest phagocytosis rate and was detected after platelet engulfment. FcR inhibition tests revealed that except for FcRIIa, FcRI and FcRIII on monocytes were responsible for the phagocytosis of anti-HPA-1a opsonized platelets. Analysis of anti-HPA-1a antibodies from FNAIT cases (n = 7) showed the phagocytosis of HPA-1aa but not of HPA-1bb platelets by monocytes. The phagocytosis rate was highly correlated with bound antibodies measured by flow cytometry (p < 0001; r = 0.9214) and MAIPA assay (p < 0.001; r = 0.7692). The phagocytosis rates were equal for type I and II anti-HPA-1a antibodies recognizing the plexin-semaphoring-integrin (PSI) domain and PSI/epidermal growth factor 1 domain of 3 integrin, respectively. By contrast, type III anti-HPA-1a antibodies reacting with v3 integrin did not induce platelet phagocytosis. Furthermore, effector-silenced mAbs against HPA-1a inhibited the phagocytosis of anti-HPA-1a opsonized platelets.In conclusion, WHOPPA is a reliable in vitro platelet phagocytosis assay that mimics the phagocytosis of anti-HPA-1a opsonized platelets in whole blood. This assay allows to prove platelet phagocytosis ex vivo and evaluate the inhibitory capacity of different inhibitors as therapeutically strategies for the prevention of fetal thrombocytopenia in FNAIT in the future.